2003
DOI: 10.1021/bi034096w
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Precision of a New H/D Exchange- and Mass Spectrometry-Based Technique for Measuring the Thermodynamic Properties of Protein−Peptide Complexes

Abstract: A new H/D exchange- and MALDI mass spectrometry-based technique, termed SUPREX, was used to characterize the thermodynamic properties of a series of model protein-peptide complexes of the Abelson tyrosine kinase SH3 domain (abl-SH3) and the S-Protein (S-Pro). The SUPREX technique was employed to evaluate the folding free energies (DeltaG(f) values) of each model protein in the absence and in the presence of a series of different peptide ligands. Ultimately, these SUPREX-derived DeltaG(f) values were used to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
111
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(113 citation statements)
references
References 38 publications
2
111
0
Order By: Relevance
“…1 as described in ref. 27. A linear least-squares analysis was used to determine the slope and y intercept of the plots of Ϫ⌬G app versus C SUPREX 1/2 that were generated for the LC8 protein and for the LC8 protein complexes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 as described in ref. 27. A linear least-squares analysis was used to determine the slope and y intercept of the plots of Ϫ⌬G app versus C SUPREX 1/2 that were generated for the LC8 protein and for the LC8 protein complexes.…”
Section: Methodsmentioning
confidence: 99%
“…However, we have previously shown that when SUPREX data obtained on nontwo-state folding proteins are well fit to Eq. 1 (as is the case with our LC8 data), the resulting ⌬G f values extracted for a given protein system can be used to generate accurate ⌬⌬G f values (27). Thus, whereas the SUPREX-derived ⌬G f values in Table 3 are not expected to be accurate, the ⌬⌬G f values in the table are expected to be reasonably accurate.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…We recently reported on a mass spectrometry-based assay for protein-ligand binding detection that utilizes an abbreviated version of stability of unpurified j;!roteins by rates of H/D exchange (SUPREX), which is an H/D exchange-and mass spectrometry-based technique capable of detecting and quantifying protein-ligand binding interactions [4][5][6][7][8][9]. In the abbreviated version of SUPREX (referred to hereafter as single-point SUPREX), binding events are detected by measuring the target protein's mass change after H/D exchange in a deuterated buffer containing a specific concentration of a chemical denaturant [10].…”
mentioning
confidence: 99%
“…In generating these complexes, proteins are mixed with their ligands in solution and the intact noncovalent complexes are observed in the gas phase for proteinsubstrate [9], protein-inhibitor [10], and intact multimeric proteins complexes [11]. Moreover, once these desolvated molecules are in the gas phase, molecular weight, binding stoichiometry, and relative/absolute binding strength can be determined using mass spectrometry [12][13][14][15][16]. Sulfotransferases, in particular, can be investigated in significant detail and information concerning the mechanism of catalysis can be garnered.…”
mentioning
confidence: 99%